2007
DOI: 10.1088/0963-0252/16/2/025
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen discharges diluted with argon: dissociation processes

Abstract: We use a global (volume averaged) model to study the dissociation processes and the presence of negative ions and metastable species in a low pressure high density O 2 /Ar discharge in the pressure range 1-100 mTorr. The electron density and the fractional dissociation of the oxygen molecule increases with increased argon content in the discharge. We relate this increase in fractional dissociation to an increase in the reaction rate for electron impact dissociation of the oxygen molecule which is due to the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
190
3
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(206 citation statements)
references
References 83 publications
9
190
3
4
Order By: Relevance
“…As a result HeþO 2 plasmas are typically operated with reduced amount of oxygen and maximum process efficacy is often encountered at oxygen concentrations below 1%. 44,45 In the last decades, global models have been used to study low-pressure electronegative plasmas [46][47][48][49] and in recent years these models have been extended to the study electronegative atmospheric-pressure discharges. [15][16][17][18] In these models it is customary to assume that the input power is mainly coupled to the electrons 50 with various approximations regarding the power coupled to ions in the sheath.…”
Section: -mentioning
confidence: 99%
“…As a result HeþO 2 plasmas are typically operated with reduced amount of oxygen and maximum process efficacy is often encountered at oxygen concentrations below 1%. 44,45 In the last decades, global models have been used to study low-pressure electronegative plasmas [46][47][48][49] and in recent years these models have been extended to the study electronegative atmospheric-pressure discharges. [15][16][17][18] In these models it is customary to assume that the input power is mainly coupled to the electrons 50 with various approximations regarding the power coupled to ions in the sheath.…”
Section: -mentioning
confidence: 99%
“…The addition of Ar increases plasma density and consequently the dissociation of oxygen molecules, since it has higher electron impact dissociation cross-section. [22] Based on results as from Figure 8B, one presumes that the etching process efficiently starts only after 2 min of exposure. Until then the functionalization with polymer bond breaking is the leading process.…”
Section: à3mentioning
confidence: 95%
“…[26] The report by Gudmundsson and Thorsteinsson, revealed that the metastable oxygen atom densities at lower pressures (below 15 Pa) increased for 15% with Ar addition (up to $43%). [27] Oxygen metastables at higher pressures (above 100 Pa) were measured by Rakhimova et al and showed that the number density of metastable oxygen molecules and atoms decreased with the increase in the concentration of argon. [28] In the case of 98% Ar gas mixture, the poor etching rate seems obvious, due to the lack of chemical assistance in the absence of dissociated O atoms.…”
Section: à3mentioning
confidence: 98%
“…In our ICP rf Argon discharge process, the pressure is 20mTorr and the flow is 200sccm, hence the corona model is valid for analyzing the process. The reason is that other collisional processes are trivial and the density of metastables is too low to make a significant contribution to the excitation of the excited species under these conditions [9][10][11]. In a corona model for these levels, we have the electron-impact excitation from the ground-state atom, Ar(gs) + e Ar(2p1 ) + e (1) and the spontaneous radiation, Ar(2p 1 )Ar(1s 2 ) + hv…”
Section: Icp Rf Dischargementioning
confidence: 99%
“…The symbol A is the Einstein coefficient, n is the density and Q exc denotes the excitation rate coefficient [11].…”
Section: Icp Rf Dischargementioning
confidence: 99%